A modified embedded-atom potential for Fe-Cr-Si alloys - Paul, Shiddartha (2022)
We developed a modified embedded atom method (MEAM) potential for Fe-Cr-Si ternary systems. These alloys have superior corrosion and crack resistance, making them candidate materials for several engineering applications such as accident-tolerant fuel cladding. We used a multiobjective optimization approach to match Fe-Cr-Si's elastic constants, ground-state energies, and structural parameters with ab initio calculations. The potential has been parameterized by fitting to a set of literature values obtained using density functional theory (DFT) or experimental studies. The developed potential was used in molecular dynamics (MD) simulations to extract mechanical and thermal properties. We obtained the calculated elastic constants for Fe-Cr-Si binary interactions using the proposed potential, agreeing with ab initio calculations. Our calculated self-diffusion coefficient values and defect formation energy using this potential are in good agreement with the previous literature. Therefore, the developed potential can investigate the fundamental behaviors on an atomic scale under harsh conditions like elevated temperature and irradiation.